2018
DOI: 10.1016/j.ympev.2017.11.025
|View full text |Cite
|
Sign up to set email alerts
|

Rapid allopolyploid radiation of moonwort ferns (Botrychium; Ophioglossaceae) revealed by PacBio sequencing of homologous and homeologous nuclear regions

Abstract: Polyploidy is a major speciation process in vascular plants, and is postulated to be particularly important in shaping the diversity of extant ferns. However, limitations in the availability of bi-parental markers for ferns have greatly limited phylogenetic investigation of polyploidy in this group. With a large number of allopolyploid species, the genus Botrychium is a classic example in ferns where recurrent polyploidy is postulated to have driven frequent speciation events. Here, we use PacBio sequencing an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 72 publications
2
52
0
1
Order By: Relevance
“…Rubus (Morden et al, 2003). Long read sequence data and the assembly of haplotypes would give additional insight into difficult-toclassify polyploid, hybrid species like R. macraei and R. chamaemorus (Kamneva et al, 2017;Dauphin et al, 2018). Haplotype sequencing could allow direct analysis of the evolutionary history of different subgenomes in these putative hybrid species with each subgenome treated as a separate branch on the phylogeny.…”
Section: Resultsmentioning
confidence: 99%
“…Rubus (Morden et al, 2003). Long read sequence data and the assembly of haplotypes would give additional insight into difficult-toclassify polyploid, hybrid species like R. macraei and R. chamaemorus (Kamneva et al, 2017;Dauphin et al, 2018). Haplotype sequencing could allow direct analysis of the evolutionary history of different subgenomes in these putative hybrid species with each subgenome treated as a separate branch on the phylogeny.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have suggested that most recognized polyploid species have multiple origins from their progenitors (D.E. Soltis & Soltis, ; Otto & Whitton, ; Mavrodiev & al., ; Fujiwara & al., ; Dauphin & al., ) and therefore have relatively high population genetic diversity. For polyploids with a single origin, genetic variation among populations is expected to be drastically reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Botrychium lunaria (Ophioglossaceae), referred to as the common moonwort, is a widespread fern distributed throughout the northern hemisphere and a few notable disjunctions to the southern hemisphere (Dauphin et al ., , , , ; Stensvold and Farrar, ). In Switzerland, B. lunaria is widespread in the Alps and Jura mountains (Maccagni et al ., ; Dauphin et al ., ). It belongs to the Ophioglossaceae family, which with its sister clade Psilotaceae, belongs to an early divergent lineage that diverged from the other ferns approximately 300 million years ago (Pryer et al ., ).…”
Section: Introductionmentioning
confidence: 99%